Design and evaluation of a polytope construct with multiple B and T epitopes against Tembusu virus infection in ducks. (February 2016) - Han, Kaikai; Zhao, Dongmin; Liu, Yuzhuo; Huang, Xinmei; Yang, Jing; Liu, Qingtao; An, Fengjiao; Li, Yin
Abstract: Tembusu virus (TMUV) is a newly emerging pathogenic flavivirus that is causing massive economic loss in Chinese poultry industry; until now, there is no effective vaccine or drug for its prevention. Epitope-based vaccination is a promising approach to achieve protective immunity and to avoid immunopathology. In present study, based on in silico epitope selection, we optimized and proposed a polytope DNA vaccine (pVAX1-rTEM) consisting B-cell and T cell epitopes from the TMUV envelope (E) protein. The immunogenicity and protective efficacy of constructed polytope DNA vaccine was assessed by in vitro and in vivo experiments. In in vitro assays, the expressed pVAX1-rTEM showed reactivity with Tembusu positive serum. Its protective efficacy against TMUV infection was evaluated in ducks. The results showed that pVAX1-rTEM was highly immunogenic and could elicit high titer neutralizing antibodies and cell-mediated immune responses. These results indicate that pVAX1-rTEM may be a promising candidate vaccine for prevention of TMUV infection. Highlights: We constructed a polytope DNA vaccine (pVAX1-rTEM). pVAX1-rTEM vaccination can elicit both humoral and cellular immune responses. This DNA vaccine might be an attractive candidate vaccine for TMUV infection.